Impact of Green Marketing on Purchase Intention: An Empirical Study from Pakistan - Rizwan, Muhammad; Aslam, Arslan; Rahman, Mujeeb ur; Ahmad, Naqash; Sarwar, Usman; Asghar, Tehseen (Asian Journal of Empirical Research, 2013)
The purpose of this study is to know the role of green perceived value, green risk and green trust on purchase intention of green product. This study applies four basic concepts of green market i.e green perceived value, green perceived risk, green perceived trust and green purchase intention. In addition, this study emphasizes this use of green marketing in different big firms all over the world. There was a survey upon this research with the help of questionnaire taking the view of the people that how different people take green marketing. The empirical results show that green perceived value is positively associated with green trust. While green perceived risk has negative relationship with both, green perceived trust and green value. Moreover, this study discusses the relationship of purchase intention of the green product with all above mentioned term of green marketing. This research paper summarizes the literature on green marketing and purchase intention of green products. It utilizes the four important concepts of green marketing i.e green perceived value, green perceived trust, green perceived risk and green purchase intention. Therefore, this paper develops the research framework of green purchase intentions to fill the research gap.